Recombinant phage displaying ToAP2D peptide with antifungal activity against Sporothrix globosa - Yan, Tianyi; An, Lin; Chen, Feng (Frontiers in Pharmacology, 2022)
We designed and synthesized recombinant phage nanofibers displaying ToAP2D peptide and investigated their antifungal effect on Sporothrix and the corresponding mechanism. Antimicrobial peptide, ToAP2D, was used as the template. The effect of synthesized recombinant phages on the immune function of CD4+ T lymphocytes in mice was tested using an enzyme-linked immunosorbent assay. The therapeutic effect and safety of recombinant phage administration on Sporothrix-infected BALB/c mice were evaluated based on survival analysis, histopathological changes, and renal and liver functions. The successfully prepared recombinant phage displaying ToAP2D peptides significantly inhibited Sporothrix growth. According to the scanning electron microscopy results, the recombinant phage caused shrinkage and rupture of Sporothrix globosa, leading to leakage of the contents. The Hoechst/propidium iodide double staining test indicated that the recombinant phage could induce cell apoptosis of Sporothrix globosa. The apoptotic pathway might be due to the accumulation of reactive oxygen species in large quantities in cells, activating caspase dependence; this reduced inflammation, prolonged the survival time, and enhanced levels of IFN-γ and IL-17 in mice. We believe that recombinant phage inhibits Sporothrix growth by adjusting the immune response of mice, inducing Sporothrix apoptosis and improving animal survival. This study offers a new approach to preparing antimicrobial peptides.